Mediation as an alternative form of pre-trial settlement of a tax dispute: doctrinal approaches and law enforcement practice - L. L. Arzumanova (Правоприменение)
The subject of research is the study of mediation procedure and embedding of mediation techniques in such a specific area of relations, the participants of which are the tax authority and the taxpayer. The settlement of tax disputes is quite understandable, since this mechanism allows to keep an economic entity on the market, on the one hand, and to replenish the state budget on the other.The purpose of the article is to confirm or disprove hypothesis that the current mechanism of pre-trial settlement of disputes established in the Russian Tax Code does not correspond to the techniques of the mediation process. The methodological basis of the research was formed by general scientific methods of cognition, which include the principles of objectivity and system analysis of the information collected during preparation of the publication. At the same time private scientific methods were also used in the work, including descriptive and comparative legal methods, which made it possible to use the practices of foreign states in terms of the use of mediation procedures. The author analyzes the official data published by the tax authority, regarding the number of disputes considered over the period of the past three years.The main scientific results, scope of application. The study made it possible to gain new knowledge in the field of legal regulation of mediation. The presented foreign experience demonstrates that at present Russia is only at the stage of formation of mediation. Most people do not yet understand what exactly the advantages of mediation. The existing procedure for the judicial settlement of a dispute attracts its participants due to the fact that the current state fees are very low compared to their foreign counterparts. All kinds of legislative transformations lead to an ambiguous interpretation of legal norms, which often defy literal interpretation, followed by conflicts in law enforcement. Since the practice of using mediation sessions is not widespread at present, a large number of debatable questions arise about the procedure for conducting mediation, the possibility of fiscal body participation, determining the categories of disputes in which negotiation techniques can be applied.Conclusions. Mediation is a systemic process that allows constructive negotiations between the parties involved in the dispute in order to resolve the problem and possibly reach an agreement on the settlement of the dispute. At the same time, it is emphasized that the lack of law enforcement practice complicates the process of researching the institution of tax mediation. The role of a mediator in legal relations (with the tax authority as a participant) is a person who must create a constructive atmosphere for discussing the conflict; adhere to the principles of mediation; assist in finding solutions without expressing his opinion on the agenda. This role of mediator is not adequately reflected in the legislation in relation to tax disputes.